New Evidence for Artemisia absinthium L. Application in Gastrointestinal Ailments: Ethnopharmacology, Antimicrobial Capacity, Cytotoxicity, and Phenolic Profile. (23rd July 2021) - Ivanov, Marija; Gašić, Uroš; Stojković, Dejan; Kostić, Marina; Mišić, Danijela; Soković, Marina
Abstract : Artemisia absinthium L. (Asteraceae) is traditionally used for gastrointestinal ailments and disorders linked to numerous risk factors including microbial infections. We aimed to provide contemporary evidence for its ethnopharmacological use and determine its antimicrobial capacity and mode of action, cytotoxicity, and phenolic constituents. Ethnopharmacological survey was conducted using semistructured interviews. Antimicrobial and antibiofilm capacities were determined by microdilution/crystal violet assay, respectively. Modes of action tested include estimation of exopolysaccharide production (congo red binding assay) and interference with membrane integrity (crystal violet uptake and nucleotide leakage assay). Cytotoxicity was determined using crystal violet assay. Polyphenolic profiling was done by advanced liquid chromatography/mass spectrometry (UHPLC-LTQ OrbiTrap MS). Artemisia absinthium in Serbia is traditionally used for gastrointestinal disorders, among others. Further study revealed high antifungal capacity of herb ethanolic extract towards range of Candida species (MIC 0.5–1 mg/mL) along with promising antibacterial activities (MIC 0.25–4 mg/mL). Interference with membrane integrity could be observed as a possible antimicrobial mechanism. Antibiofilm potential can be considered as high (towards C. krusei ) to limited (towards P. aeruginosa ) and moderate based on reduction in exopolysaccharide content. In concentrations up to 400 µ g/mL, no cytotoxicity was observed towards HaCaT and HGF-1 cell lines. Polyphenolic analysis revealed twenty-one different constituents. A. absinthium usage as a gastrointestinal ailment remedy has been confirmed in vitro by its antimicrobial capacity towards microorganisms whose presence is linked to the diseases and associated complications and noncytotoxic nature of the natural product. The observed activities could be attributed to the present phenolic compounds.